Тарас Шевченко в рецепції Дмитра Павличка - Теребус, Оксана; Terebus, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано публіцистичні та літературознавчі статті Д. Павличка, присвячені творчості Т. Шевченка. Д. Павличко протягом багатьох років повертається до постаті титана української літератури, що не тільки зробив потужний внесок у літературу, а й став світочем українського духу. Також публіцист підкреслює важливість традицій та наставництва, суголосності тем у творчості Т. Шевченка та молодшого покоління українських літераторів. The article analyzes journalistic and literary articles by Dmytro Pavlychko, as well as articles dedicated to works of Taras Shevchenko. For many years, Pavlychko has turned to the master of Ukrainian literature, who not only made a significant contribution to the literature, but also became a vivid representation of Ukrainian spirit. The author assesses the artist’s works and highlights an unusual approach to the understanding of ideology, citizenship and human intelligence in general through the image of Shevchenko. The writer stresses the importance of traditions and mentoring, unanimity of themes in Shevchenko’s works and the younger generation of Ukrainian writers.The publicist describes him in the context of contemporary spiritual needs, directed his ideas to our time and ourselves. Pavlychko dialectically considers the spiritual heritage of the poet in the relation to the current literature stage and role of the artist in the national and international literature.
Dmytro Pavlychko’s outlook on Shevchenko
Keywords: збірки літературно-критичних та публіцистичних статей; стаття-виступ; стаття-промова; суголосність тем; the collection of literary-critical and journalistic articles; article-address; article-speech; unanimity of topics